2015
DOI: 10.1007/s11103-015-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of a rice microtubule-associated RING finger protein and its potential role in salt tolerance in Arabidopsis

Abstract: Although a number of RING E3 ligases in plants have been demonstrated to play key roles in a wide range of abiotic stresses, relatively few studies have detailed how RING E3 ligases exert their cellular actions. We describe Oryza sativa RING finger protein with microtubule-targeting domain 1 (OsRMT1), a functional RING E3 ligase that is likely involved in a salt tolerance mechanism. Functional characterization revealed that OsRMT1 undergoes homodimer formation and subsequently autoubiquitination-mediated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…B). Our previous studies revealed that most proteins interacting with the rice RING E3 ligases serve as substrates (Lim et al , Lim et al , Park et al ). Similarly, the present results also show that OsAIR2 ubiquitinates OsKAT1 leading to a reduction in the protein levels of OsKAT1 via 26S proteasome degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B). Our previous studies revealed that most proteins interacting with the rice RING E3 ligases serve as substrates (Lim et al , Lim et al , Park et al ). Similarly, the present results also show that OsAIR2 ubiquitinates OsKAT1 leading to a reduction in the protein levels of OsKAT1 via 26S proteasome degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the O. sativa RING finger protein with microtubule‐targeting domain 1 (OsRMT1) binding to its substrate proteins OsSalT, OsCPA, OsFKBP12, and OsDH1 results in protein degradation via the 26S proteasome system. However, transcript levels of these substrate genes were highly increased in response to salt stress (Lim et al ). Similarly, the partner genes of another gamma ray‐induced E3 ligase OsGIRP1, namely OsrbcL1 and OsrbcS1, were also highly induced when exposed to gamma ray irradiation, followed by the degradation of these substrate proteins by OsGIRP1 via the 26S proteasome pathway (Park et al ).…”
Section: Discussionmentioning
confidence: 99%
“…RING E3 ligases can interact and regulate multiple substrate proteins in a diverse functional network (Iconomou & Saunders, ; Lim et al, ; Lim et al, ). OsSIRH2‐14 E3 ligase interacts with multiple substrates, including OsSalT, OsPRF2, and OsHKT2;1 (Lim et al, ; Figures and S7).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the reduced Na + accumulation in OsSIRH2-14-overexpressing plants might lead to decreased oxidative damage and increased capacity for proline and soluble sugars. RING E3 ligases can interact and regulate multiple substrate proteins in a diverse functional network (Iconomou & Saunders, 2016;Lim et al, 2013;Lim et al, 2015). OsSIRH2-14 E3 ligase interacts with multiple substrates, including OsSalT, OsPRF2, and OsHKT2;1 (Lim et al, 2013;Figures 4 and S7).…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins were extracted from 3-week-old seedlings. Tissue samples (500 mg) were quickly incubated with 1 mL of modified denaturing buffer [50 mM 2-amino-2-(hydroxymethyl)-1,3-propanediol-HCl, pH 7.5, 250 mM NaCl, 0.1% IGEPAL CA-630, 4 M urea, 10 mM NaPO4, pH = 6.0, and 19 protease inhibitor cocktail (Roche Applied Science, Indianapolis, IN)] for 10 min and were centrifuged for 30 min at 16 000 9 g at 4°C for 30 min (Lim et al, 2015). The soluble supernatant fraction was moved to a new microcentrifuge tube, and protein concentration was determined using the Pierce BCA Protein Assay Kit (Thermo Fisher Scientific, Rockford, IL).…”
Section: Protein Extraction and Immunoblot Analysismentioning
confidence: 99%